Prognostic implications of myocardial perfusion imaging and coronary calcium score in a Macedonian cohort of asymptomatic patients with type 2 diabetes. (July 2017) - Mitevska, Irena Peovska; Baneva, Natalija; Srbinovska, Elizabeta; Stojanovska, Lily; Apostolopoulos, Vasso; Bosevski, Marijan
Aim: Type 2 diabetes is a risk factor for coronary artery disease; however, a number of studies have shown that patients are asymptomatic for coronary artery disease. The presence of coronary artery disease in asymptomatic patients with type 2 diabetes was evaluated to determine its impact on management decision and prognosis. Methods: A total of 75 patients underwent single-photon emission computed tomography myocardial perfusion imaging for detection of suspected coronary artery disease. We used 17-segment model for perfusion and function analysis. Multislice computed tomography was performed in 45 patients to assess coronary artery calcium. Complete laboratory analyses with lipid values and standard risk factors were analysed. Forward logistic regression analysis was used to assess predictive parameters for myocardial ischaemia during the follow-up period of 20 ± 4 months. Results and Conclusion: Silent myocardial ischaemia and subclinical coronary artery disease can be detected in a significant proportion of asymptomatic patients with type 2 diabetes. Diabetic patients with normal myocardial perfusion imaging had an excellent 2-year prognosis with optimal medical therapy and intensive risk factor control. In comparison, an abnormal myocardial perfusion imaging led to an increased risk of cardiovascular events. Myocardial perfusion imaging and coronary artery calcium are valuable tools for risk stratification and optimal treatment decision in this asymptomatic diabetic cohort of Macedonian patients.